Pengaruh Stress Kerja, Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Inline Flow Specialty - Amalia, Lisa; Sriwahyuni, Etty; Wibisono, Chablullah (Universitas Batam, 2022)
The purpose of this study was to determine and analyze the effect of work stress, work environment and workloads on employee’s performance partially and simultaneously. The population in this study were employees of PT. Inline Flow Specialty as many as 52 employees. Data collection was carried out through distributing questionnaires and analyzing the data obtained using quantitative data analysis. Quantitative analysis includes: Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis testing through t test and F test, and coefficient of determination (R2), Data processing with the help of SPSS 21 Software. The data that have met the validity, reliability and classical assumption test from the results of multiple linear regression test obtained by the following equation: Y = 19,439+ (-0.244X1)+0.834X2+0.102X3+e From the results of the t test (partial) it shows that work stress has a significant effect on performance, work environment has a significant effect on performance, and workloads has no significant effect on performance and simultaneously work stress, work environment and workloads have a significant effecton Performance. The results of the coefficient of determination test (R2) are known that 24.6% of the variation in performance can be explained by the variables of Work Stress, Work Environment and Workloads. While the remaining 75.4% (100% - 24.6%) was applied by other variables that were not proposed in this study.